Silica bodies of grasses from the "cerrado". II - Campos, Antonio Constantino de; Labouriau, Luiz Gouvêa (Pesquisa Agropecuaria Brasileira, 2014)
The morphology of silica bodies was studied for ten species of grasses from the "Cerrado" flora (several types of savannah of Central Brazil): Eragrostis reptans (Michx.) Nees, Eriochloa distachya H.B.K., Paspalum barbatum Nees, P. Polyphyllum Nees, P. carinatum H. & B., P. falcatum Nees, P. maculosum Trin., P. neesii Kunth, P. rojasii Hack., P. trachycoleon Steud. Parts of the identified material were washed, dried and charred in closed porous clay crucibles for 2 hours at 200°C in an electric oven. The residue was boiled for ten minutes in 5N HCl, filtered over ash less filter paper and washed with distilled water until no more chloride ion was detectable, in successive washings, by a drop test with 1% aqueous AgNO3. The washed material, wrapped in the filter paper disc, was dried and ignited, in another porous clay crucible closed by an identical crucible, at 800°C for 2 hours. Aliquots from the siliceous residue thus obtained were mounted in Canada balsam for microscopic study. Blanks were used to check on possibles artifacts from dust and other sources for contamination. It turns out that artifacts are easily detected as they are strongly birefringent, whereas the phytogenic silica is invariably an opalescente silica, amorphous and without tension, that completely disappears from the microscopic field upon crossing nicols. The shapes of silica bodies were drawn with a camera lucida, documented by figures and grouped by species. The frequent occurrence of whole epidermal plates indicates the massive silicification of leaves of these grasses. Not only short-cells, but also long-sells, stomates, hairs, papillose cells, bulliform cells and even xylem element smay be completely silicified. Possible consequences of these observations are discussed in connection with the prospects of using this information for the study of autoecological problems in the Brazilian "Cerrados" as well as for synecological question bearing on the historical oscilations of boundaries between "Cerrado"-vegetation and other types of contiguous plant formations.